COMPANY STOCK PERFORMANCE ANALYSIS AFTER initial public offering STOCK EXCHANGE IN JAKARTA - Suratiningsih, Suratiningsih; Lastari., SE., MM, Siwi (Management, 2010)
The stock market is a market for various financial instruments or long-term securities that can be traded in the form of money or capital, whether issued by governments, and private enterprise development of securities trading activities in the Indonesian capital market is increasingly attractive to be studied or examined in a study . Trading securities or securities attractive to investors, because security is a piece of paper that shows the right investor (investor) to acquire part of the prospect or long-term wealth in a company that publishes and likely provides great benefits and substantial risks. For companies, to attract buyers and sellers to participate, capital markets must be liquid and efficient. A liquid is said to capital markets if the seller can sell and buyers can purchase the securities quickly. Capital markets said to be efficient if the price of securities reflects the value of the firm accurately. Investors invest their funds because the investment is the commitment of a number of funds or other resources committed at this point in order to gain some advantage in the years to come. One of the company´s efforts to add additional capital to enhance the operational activities of the company through an Initial Public Offering (IPO). At the time of IPO companies that went public are required to create and publish a prospectus in a newspaper of national standards according to provisions established by the Capital Market Supervisory Agency (Bapepam). keyword: capital,operational,invest